![image](https://tex.z-dn.net/?f=%5C%5Clg%28x%2B3%29%3E0%2C+%5C+x%3E-3%0A%5C%5C%0A%5C%5Clg%28x%2B3%29%3Elg1%0A%5C%5C%0A%5C%5Cx%2B3%3E1%0A%5C%5C%0A%5C%5Cx%3E-2%0A%5C%5C%0A%5C%5Cx%5Cin%28-2%2C%2B%5Cinfty%29%0A%5C%5C%0A%5C%5C2sinx-1%3D0%0A%5C%5C%0A%5C%5Csinx%3D%5Cfrac12%0A%5C%5C%0A%5C%5Cx%3D%5Cfrac%5Cpi6%2B2n%5Cpi+%5C+%5Cvee+%5C+x%3D%28%5Cpi-%5Cfrac%5Cpi6%29%2B2n%5Cpi%3D%5Cfrac%7B5%5Cpi%7D%7B6%7D%2B2n%5Cpi%2C+%5C+n%5Cin+Z)
0, \ x>-3
\\
\\lg(x+3)>lg1
\\
\\x+3>1
\\
\\x>-2
\\
\\x\in(-2,+\infty)
\\
\\2sinx-1=0
\\
\\sinx=\frac12
\\
\\x=\frac\pi6+2n\pi \ \vee \ x=(\pi-\frac\pi6)+2n\pi=\frac{5\pi}{6}+2n\pi, \ n\in Z" alt="\\lg(x+3)>0, \ x>-3
\\
\\lg(x+3)>lg1
\\
\\x+3>1
\\
\\x>-2
\\
\\x\in(-2,+\infty)
\\
\\2sinx-1=0
\\
\\sinx=\frac12
\\
\\x=\frac\pi6+2n\pi \ \vee \ x=(\pi-\frac\pi6)+2n\pi=\frac{5\pi}{6}+2n\pi, \ n\in Z" align="absmiddle" class="latex-formula">